Environmental Impacts of Mechanized Timber Harvesting in Eucalyptus Plantations in Brazil - Ferraz, Camila Porfirio Albuquerque [UNESP]; Manoel, Márcia Pereira da Silva [UNESP]; Chaves, Jô Vinícius Barrozo [UNESP]; Aiello, Luiz Henrique Freguglia [UNESP]; Silva, Gislene Sales da [UNESP]; De Medeiros, Gerson Araújo [UNESP]; Ribeiro, Admilson Írio [UNESP] (MDPI, 2024)
The advancement of mechanization in forestry has increased productivity in the forestry sector, bringing positive and negative impacts that require a deeper understanding for sustainable forest management. This study aimed to apply a simplified instrument for assessing damage and environmental impacts in forest harvesting of commercial eucalyptus plantations, using a combination of methodologies. The methodology used combined interaction networks and impact assessment matrices, carrying out field surveys, transposing them to interaction networks and weighting them through assessment matrices, resulting in environmental indices (ES) for prioritizing actions. The study was conducted on a commercial eucalyptus plantation in the municipality of São Pedro, São Paulo, Brazil. The mechanized harvesting of the area consists of the structure of a module with a mobile unit consisting of a harvester and forwarder. The results indicated that wood transport presented the highest ES, both positive and negative. The most significant negative impacts (ES) were the depletion of water resources and erosion, while the positive impacts included regional development and job creation. The most notable changes, positive and negative, were observed in the physical and anthropic environment, with a lesser impact on the biotic environment.
Keywords: eucalyptus plantation; forestry; harvest forest planning; interaction networks; mechanized timber harvesting; sustainable forest management